International Encyclopedia of the Social &Amp; Behavioral Sciences 2015
DOI: 10.1016/b978-0-08-097086-8.22006-0
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Deviance

Abstract: Workplace deviance is a serious and costly problem for organizations. This encyclopedia article outlines the growing body of scholarly research investigating these counterproductive workplace behaviors. Researchers have identified two main dimensions underlying deviant workplace behaviors. Numerous antecedents increase the likelihood and affect the target of workplace deviance. Multiple techniques deter, reduce, and/or prevent employees from participating in workplace deviance. However, these methods may come … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The review of past studies indicated that CWB is associated with numerous employee attitudes and behaviours. It is also a reality that majority of employees in organizations, to a certain extent, engage in CWB, which costs organizations billions of dollars arising from productivity loss and other harmful consequences (Bennett et al, 2019, as cited in Mackey et al, 2019. This indicates a need for scholars and managers to find a means to reduce employees' CWB in order to prevent organizations from its negative consequences.…”
Section: Workplace Spirituality and Counterproductive Work Behaviourmentioning
confidence: 99%
“…The review of past studies indicated that CWB is associated with numerous employee attitudes and behaviours. It is also a reality that majority of employees in organizations, to a certain extent, engage in CWB, which costs organizations billions of dollars arising from productivity loss and other harmful consequences (Bennett et al, 2019, as cited in Mackey et al, 2019. This indicates a need for scholars and managers to find a means to reduce employees' CWB in order to prevent organizations from its negative consequences.…”
Section: Workplace Spirituality and Counterproductive Work Behaviourmentioning
confidence: 99%
“…The literature on workplace deviance or counterproductive behaviour is growing, which suggests that such a phenomenon, if not managed well, is likely to affect the organisation and its members negatively (Bennett and Marasi, 2015). Workplace deviance can be understood as acts that are against the norms and expectations of the organisation that could harm its well-being and stakeholders (Bennett et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational CWBs 9 include such behaviors as missing work appointments, complaining about insignificant things at work, and misuse of firm resources (Robinson & Bennett, 1995). A large body of research has focused on understanding antecedents of deviant behavior, including individual characteristics and situational factors (Mackey, McAllister, Ellen, & Carson, 2019), however, this literature stream focuses primarily on understanding a singular type of specific behavior (Bennett & Marasi, 2015). Bennett and Marasi (2015, p. 723) suggest that studying a broader theoretical conceptualization of deviant behaviors, such as CWBs aimed at the organization, facilitates identification of "an underlying root cause [that] provides theoretical integration."…”
Section: Cwbs and Self-focused Work Climatesmentioning
confidence: 99%
“…The literature (e.g.,Bennett & Marasi, 2015) uses "deviant behavior" and "CWBs" interchangeably, as we do in this paper.10 We explicitly do not equate a low level of self-focused work climate with an other-focused work climate. This has both theoretical and empirical reasons.…”
mentioning
confidence: 99%